Hydrocarbon adsorbent for exhaust gas, its manufacturing method, and HC trap for exhaust gas purification

The K-X-supported MSE zeolite addresses the poor desorption issue of conventional hydrocarbon adsorbents by enhancing HC desorption initiation temperature, resulting in improved HC purification performance during cold starts in internal combustion engines.

JP7602938B2Active Publication Date: 2024-12-19N E CHEMCAT
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021035144
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-05
Publication Date
2024-12-19
Estimated Expiration
2041-03-05

AI Technical Summary

Technical Problem

Conventional hydrocarbon adsorbents for exhaust gas exhibit poor HC desorption performance, leading to insufficient HC purification during cold starts in internal combustion engines.

Method used

A hydrocarbon adsorbent using K-X-supported MSE zeolite with specific silica-alumina and potassium ratios, along with additional elements like Cs, Rb, Ba, Sr, Ti, V, Cr, Mn, Fe, Co, Ni, Zr, Mo, Cu, or Au, enhances HC desorption initiation temperature and purification performance.

Benefits of technology

The K-X-supported MSE zeolite exhibits high HC desorption start temperature and improved HC purification performance at cold starts, enabling efficient exhaust gas purification systems with industrial simplicity and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602938000001
    Figure 0007602938000001
Patent Text Reader

Abstract

To provide a hydrocarbon adsorbent for exhaust that is high in HC desorption start temperature of adsorbed HC, and can express higher HC purification performance at a cold start, and a method for producing the same, and an HC trap for exhaust purification.SOLUTION: A hydrocarbon adsorbent for exhaust at least contains an MSE-type zeolite, and potassium and X supported on the MSE-type zeolite (where X is at least one element selected from the group consisting of alkali metals, alkaline-earth metals, and transition metals, excluding K). The MSE-type zeolite has a silica-alumina ratio (SiO2 / Al2O3) of 10 or more and 100 or less in molar ratio, and the ratio of X to potassium (X / K) is 2.0 or more and 25.0 or less in molar ratio.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adsorbent for exhaust gas hydrocarbons, a method for producing the same, and an HC trap for exhaust gas purification. [Background technology]

[0002] Exhaust gas from internal combustion engines of automobiles and other vehicles contains hydrocarbons (HC), nitrogen oxides (NOx), carbon monoxide (CO), and particulate matter (PM), and these are efficiently purified by exhaust gas purification systems equipped with various exhaust gas purification catalysts developed according to the type of internal combustion engine.

[0003] However, for example, many of the HC purification performance of exhaust gas purification catalysts for internal combustion engines show sufficient catalytic activity at a catalyst temperature of around 200°C. Therefore, when the exhaust gas purification catalyst has not yet reached a temperature at which it shows sufficient catalytic activity, it does not exhibit the expected exhaust gas purification performance. Therefore, for example, during a cold start, such as immediately after starting the engine, it is expected that there may be cases where HC emissions are high.

[0004] For this reason, improvements to the purification performance of HC emitted at low temperatures in internal combustion engines are being studied.Specifically, a method is known in which HC contained in exhaust gas is temporarily trapped (adsorbed, held) in a hydrocarbon adsorbent until the exhaust gas purification catalyst is warmed up to a temperature at which it exhibits sufficient catalytic activity, and then HC is gradually desorbed from the hydrocarbon adsorbent as the catalyst temperature rises, and then purified by the exhaust gas purification catalyst, thereby improving HC purification performance.

[0005] As such hydrocarbon adsorbents for exhaust gas, those using various zeolites are known. For example, Patent Document 1 discloses a gas component reducing material in which Ag is supported on β-type zeolite having a silica-alumina ratio (silica-alumina ratio) of 120 or more or 200 or more in order to enhance heat resistance.

[0006] Furthermore, Patent Document 2 discloses that a hydrocarbon adsorbent for exhaust gas made of a multidimensional pore zeolite having two-dimensional pores and / or three-dimensional pores composed of 12-membered rings and / or 10-membered rings (ISV structure zeolite, BEC structure zeolite, MCM-68 (MSE structure zeolite), MWW structure zeolite) exhibits a higher HC adsorption rate than β-type zeolite.

[0007] On the other hand, Patent Document 3 discloses a catalyst layer containing a composition in which an active metal selected from potassium, rubidium, cesium, beryllium, magnesium, calcium, barium, strontium, or a mixture of any two or more of them is impregnated onto a hydrocarbon adsorption material, and specifically, it shows that the HC purification performance is improved by impregnating ZSM-5 (MFI type zeolite) with cesium.

[0008] Furthermore, Patent Document 4 discloses that the HC adsorption and purification performance is improved by including a special intercalation compound prepared using a host compound and a guest substance in the HC adsorption layer. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2002-001109 A [Patent Document 2] JP 2004-105821 A [Patent Document 3] Special Publication No. 2004-504130 [Patent Document 4] JP 2006-297375 A Summary of the Invention [Problem to be solved by the invention]

[0010] However, the above-mentioned conventional hydrocarbon adsorbents for exhaust gas are inferior in terms of the release performance of trapped HC, and therefore the HC purification performance during cold start is still insufficient.

[0011] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a hydrocarbon adsorbent for exhaust gas which has a high HC desorption start temperature for adsorbed HC and is capable of exhibiting high HC purification performance at cold start, a method for producing the same, and an HC trap for exhaust gas purification, etc.

[0012] In addition to the objectives stated here, the present invention can also be positioned as another objective of achieving effects that are derived from the various components shown in the description of the embodiments of the invention described below, and that cannot be obtained by conventional techniques. [Means for solving the problem]

[0013] As a result of intensive research into solving the above-mentioned problems, the inventors have found that KX-supported MSE zeolite, in which a specific element is supported on MSE zeolite, has a high HC desorption onset temperature of adsorbed HC and can exhibit higher HC purification performance at the time of cold start, and have also found that the above-mentioned problems can be solved by using this as a hydrocarbon adsorbent for exhaust gas, which has led to the completion of the present invention.

[0014] That is, the present invention provides various specific embodiments as shown below. [1] An adsorbent for hydrocarbons for exhaust gas comprising: an MSE zeolite; and potassium and X (wherein X is one or more elements selected from the group consisting of alkali metals other than K, alkaline earth metals, and transition metals) supported on the MSE zeolite, wherein the MSE zeolite has a silica-alumina ratio (SiO2 / Al2O3) of 10 or more and 100 or less in molar ratio, and X has a potassium ratio (X / K) of 2.0 or more and 25.0 or less in molar ratio.

[0015] [2] The hydrocarbon adsorbent for exhaust gas according to [1], wherein the potassium to alumina ratio (K / Al) is 0.04 or more and 0.50 or less in molar ratio.

[0016] [3] The adsorbent for exhaust gas hydrocarbons according to [1] or [2], wherein the alumina ratio (X / Al) of X is 0.10 or more and 1.50 or less in terms of molar ratio.

[0017] [4] The adsorbent for exhaust gases using hydrocarbons according to any one of [1] to [3], which has a crystallite size of 10 nm or more and 100 nm or less in powder X-ray diffraction measurement.

[0018] [5] The adsorbent for exhaust gases using hydrocarbons according to any one of [1] to [4], which has an average particle size D50 of 0.01 μm or more and 20 μm or less.

[0019] [6] The adsorbent for exhaust gas hydrocarbons according to any one of [1] to [5], wherein X is one or more selected from the group consisting of Cs, Rb, Ba, Sr, Ti, V, Cr, Mn, Fe, Co, Ni, Zr, Mo, Cu, Ag, and Au.

[0020] [7] An HC trap for exhaust gas purification used in an exhaust gas purification system for purifying exhaust gas from an internal combustion engine, the HC trap for exhaust gas purification comprising a honeycomb type substrate and a hydrocarbon adsorption layer provided on and / or within the honeycomb type substrate, the hydrocarbon adsorption layer containing at least the hydrocarbon adsorbent for exhaust gas according to any one of [1] to [6].

[0021] [8] The HC trap for purifying exhaust gas according to [7], wherein the hydrocarbon adsorption layer contains 1 g / L or more and 150 g / L or less of the exhaust gas hydrocarbon adsorbent, based on a unit volume (1 L) of the honeycomb substrate.

[0022] [9] The hydrocarbon adsorption layer The precious metal component is selected from the group consisting of Pt, Pd, and Rh. The exhaust gas purifying agent according to [7] or [8], wherein the hydrocarbon adsorption catalyst layer comprises one or more selected from the group consisting of HC trap for chemical use.

[0023]

[10] The HC trap for purifying exhaust gas according to any one of [7] to [9], further comprising a catalyst layer.

[0024]

[11] A method for producing a KX-supported MSE zeolite, comprising at least a step of preparing a K-supported MSE zeolite, and a step of adding X (wherein X is one or more elements selected from the group consisting of alkali metals other than K, alkaline earth metals, and transition metals) to the K-supported MSE zeolite to synthesize a KX-supported MSE zeolite.

[0025]

[12] The method for producing a KX-supported MSE zeolite according to

[11] , wherein in the step of synthesizing the KX-supported MSE zeolite, the X is supported on the K-supported MSE zeolite by an ion exchange method.

[0026]

[13] The method for producing a KX-supported MSE zeolite according to

[11] or

[12] , wherein in the step of preparing the K-supported MSE zeolite, the K-supported MSE zeolite is synthesized by a hydrothermal synthesis method in the presence of potassium. Effect of the Invention

[0027] According to the present invention, it is possible to realize an exhaust gas hydrocarbon adsorbent or the like that has a high HC desorption start temperature for adsorbed HC and is capable of exhibiting high HC purification performance during cold start, thereby realizing an exhaust gas purification HC trap or exhaust gas purification HC trap catalyst or the like that has excellent purification performance. Furthermore, according to the present invention, such a high-performance exhaust gas hydrocarbon adsorbent can be supplied by an industrially simple process and at a relatively low cost. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] Hereinafter, the embodiments of the present invention will be described in detail. The following embodiments are examples (representative examples) of the present invention, and the present invention is not limited to these. The present invention can be modified as desired without departing from the scope of the present invention. In this specification, when a numerical value or physical property value is enclosed before and after "~", the values ​​before and after the "~" are included. For example, the expression of a numerical range of "1 to 100" includes both the lower limit "1" and the upper limit "100". The same applies to the expression of other numerical ranges.

[0029] [Hydrocarbon adsorbent for exhaust gas] The hydrocarbon adsorbent for exhaust gas of the present embodiment contains at least MSE zeolite, and potassium and X (wherein X is one or more elements selected from the group consisting of alkali metals other than K, alkaline earth metals, and transition metals) supported on the MSE zeolite, and is characterized in that the silica-alumina ratio (SiO2 / Al2O3) of the MSE zeolite is, in molar ratio, 10 or more and 100 or less, and the potassium ratio (X / K) of X is, in molar ratio, 2.0 or more and 25.0 or less.

[0030] MSE type zeolite is an aluminosilicate given the framework type code MSE by the International Zeolite Association (hereinafter sometimes abbreviated as "IZA"). MSE type zeolite has a three-dimensional pore structure specific to MSE, in which large pores (12-membered ring pores) and medium pores (10-membered ring pores) intersect three-dimensionally, and has a relatively large surface area and large internal space, so that its molecular sieving action gives it a high adsorption capacity for hydrocarbons (HCs) such as benzene, toluene, xylene, and benzaldehyde. The structure of this MSE type zeolite can be identified by comparing it with either the powder X-ray diffraction (hereinafter referred to as "XRD") pattern described in Collection of simulated XRD powder patterns for zeolites, Fifth revised edition (2007) or the XRD pattern described in Zeolite Framework Types on the IZA Structure Committee's homepage http: / / www.iza-struture.org / databases / .

[0031] The silica-alumina ratio (SiO2 / Al2O3, molar ratio, hereinafter sometimes simply referred to as "SAR") of MSE type zeolite can be appropriately set according to the desired performance, and is not particularly limited, but is generally preferably 10 to 100 in molar ratio, more preferably 15 to 80, and even more preferably 18 to 60. In this specification, the silica-alumina ratio means a value obtained from fluorescent X-ray analysis. Specifically, a sample obtained by pressurizing about 5 g of a sample at 20 t using Axios (Spectolysis) was subjected to measurement, and the SAR was calculated from the results of the mass % of SiO2 and Al2O3 obtained. A large silica-alumina ratio tends to have excellent hydrothermal resistance, and is therefore expected to be used in applications exposed to high-temperature exhaust gas. On the other hand, a small silica-alumina ratio tends to have excellent hydrophilicity and a high acid amount, and is therefore expected to show high activity as a solid acid catalyst.

[0032] The MSE zeolite used here is not particularly limited, but from the viewpoint of thermal durability and catalytic performance, it is preferable that the MSE zeolite has a crystallite size of 10 nm or more and 100 nm or less, more preferably 15 nm or more and 90 nm or less, and even more preferably 20 nm or more and 80 nm or less, as measured by powder X-ray diffraction.

[0033] When used in the form of powder, the particle size of the MSE zeolite can be appropriately set according to the required performance and is not particularly limited, but from the viewpoint of surface area, handling, etc., the average particle size D50 is preferably 0.01 μm to 20 μm, more preferably 0.1 to 18 μm, and even more preferably 0.5 μm to 15 μm. In this specification, the average particle size D50 means the median diameter measured by a laser diffraction particle size distribution measuring device (for example, Shimadzu Corporation's laser diffraction particle size distribution measuring device SALD-3100, etc.). The particle shape of the zeolite is not particularly limited, and may be, for example, a rectangular parallelepiped, spherical, ellipsoidal, crushed, flat, irregular shape, etc.

[0034] The BET specific surface area of ​​the MSE zeolite can be appropriately set depending on the required performance, and is not particularly limited. 2 / g or more 1000m 2 / g or less is preferable, and 300m 2 / g or more 800m 2 / g or less is more preferable, and 300m 2 / g or more 600m 2 / g or less is more preferable.

[0035] The MSE type zeolite can be synthesized by a method known in the art, and the synthesis method is not particularly limited. As a representative synthesis method, for example, a method of hydrothermal synthesis from a mixture (raw material composition) containing a silica source (e.g., colloidal silica, silica gel, sodium silicate, etc.), an alumina source (or silica-alumina source), an alkali metal source such as an alkali metal hydroxide (e.g., NaOH, KOH, etc.), an organic structure directing agent OSDA (e.g., tetraethylammonium ions such as tetraethylammonium hydroxide, tetraethylammonium bromide, and tetraethylammonium chloride; N,N,N',N'-tetraalkylbicyclo[2,2,2]oct-7-ene-2,3:5,6-dipyrrolidinium diiodide, etc.; 1,1-dimethyl-1-azonia-4-aza-4-cyclohexylcyclohexane; dimethyldipropylammonium, etc.), and water, etc. is known. The treatment temperature (reaction temperature) of the hydrothermal synthesis is not particularly limited, but is usually 100°C to 200°C, preferably 120°C to 190°C, and more preferably 150°C to 180°C, from the viewpoint of the crystallinity and economic efficiency of the obtained MSE zeolite. The treatment time (reaction time) of the hydrothermal synthesis is not particularly limited as long as it is long enough for crystallization to occur, but is usually 1 hour to 20 days, preferably 4 hours to 16 days, and more preferably 12 hours to 14 days, from the viewpoint of the crystallinity and economic efficiency of the obtained MSE zeolite. After the synthesis, the target MSE zeolite can be obtained by performing a solid-liquid separation treatment, a water washing treatment, a drying treatment for removing moisture in the air at a temperature of about 50 to 150°C, or the like, according to a conventional method, as necessary. Alternatively, MSE zeolite can be synthesized by using an already synthesized MSE zeolite as a seed crystal (seed crystal) without using OSDA and hydrothermally synthesizing a mixture containing FAU zeolite as a silica-alumina source, an alkali metal source such as NaOH or KOH, and water. From the viewpoints of ease of synthesis and economic efficiency, it is preferable to synthesize MSE zeolite by hydrothermal synthesis in the presence of potassium as an alkali metal source.

[0036] In addition, the MSE zeolite after synthesis may contain an organic structure-directing agent or an alkali metal in the pores. Therefore, if necessary, the organic structure-directing agent may be removed by performing a liquid phase treatment using an acidic aqueous solution, a liquid phase treatment using a chemical solution containing a decomposition component of the organic structure-directing agent, an exchange treatment using a resin, or a calcination treatment at 400°C to 800°C, preferably 450°C to 750°C. These treatments may be performed in any combination. Among these, the organic structure-directing agent is preferably removed by a calcination treatment from the viewpoint of production efficiency. The treatment time (calcination time) in the calcination treatment may be appropriately set according to the treatment temperature and economic efficiency, and is not particularly limited, but is usually 0.5 hours to 72 hours, preferably 1 hour to 48 hours, and more preferably 3 hours to 40 hours.

[0037] The above-mentioned zeolite may have metal ions such as alkali metal ions on its ion exchange sites. Depending on the desired performance, an ion exchange step may be carried out. In this ion exchange step, ammonium ions (NH4 + ) and protons (H + ) or other nonmetallic cations. For example, MSE zeolite can be ion-exchanged into the ammonium type by performing a liquid phase treatment using an aqueous solution containing ammonium ions, such as an aqueous ammonium nitrate solution or an aqueous ammonium chloride solution. In addition, MSE zeolite can be ion-exchanged into the proton type by performing a calcination treatment after ion-exchanging with ammonia. Furthermore, if necessary, a treatment to reduce the amount of acid can be further performed. The treatment to reduce the amount of acid can be performed, for example, by silylation, steam treatment, dicarboxylic acid treatment, or the like.

[0038] The hydrocarbon adsorbent for exhaust gas of this embodiment contains at least potassium and X (here, X is one or more elements selected from the group consisting of alkali metals other than K, alkaline earth metals, and transition metals) supported on MSE zeolite. Here, K and X can be present in the form of an oxide or composite oxide, or in the form of an ion at the zeolite adsorption site. MSE zeolite supporting potassium and X in this way has a higher HC desorption start temperature of adsorbed HC compared to MSE zeolite not supporting potassium and X, and can retain HC in the pores until the temperature becomes relatively high, and can suppress desorption of HC until just before the temperature (for example, around 200°C) at which sufficient catalytic activity is exhibited, so that higher HC purification performance can be exhibited at the time of cold start.

[0039] The potassium supported on the MSE zeolite may be supported on the MSE zeolite by the above-mentioned hydrothermal synthesis, or may be provided (supported) separately on the MSE zeolite after synthesis. Potassium can be supplied as, for example, sulfate, nitrate, acetate, chloride, oxide, composite oxide, complex salt, or the like. The method for supporting potassium on the MSE zeolite after synthesis may be carried out according to a conventional method, and is not particularly limited, but examples thereof include an ion exchange method, an evaporation to dryness method, a precipitation support method, a physical mixing method, and an impregnation support method. After the potassium support treatment, if necessary, a solid-liquid separation treatment, a water washing treatment, a drying treatment for removing moisture at a temperature of, for example, about 50 to 150°C in the air, and the like can be carried out according to a conventional method.

[0040] The amount of potassium supported can be appropriately set depending on the required performance and is not particularly limited, but the potassium to alumina ratio (K / Al) is preferably 0.04 or more and 0.50 or less, more preferably 0.04 or more and 0.45 or less, and even more preferably 0.05 or more and 0.40 or less, in terms of molar ratio.

[0041] Examples of X supported on the MSE zeolite include, but are not limited to, alkali metals other than K (potassium), such as Li (lithium), Na (sodium), Rb (rubidium), and Cs (cesium); alkaline earth metals such as Be (beryllium), Mg (magnesium), Ca (calcium), Sr (strontium), and Ba (barium); transition elements present between Group 3 elements and Group 11 elements in the periodic table, such as Sc (scandium), Ti (titanium), V (vanadium), Cr (chromium), Mn (manganese), Fe (iron), Co (cobalt), Ni (nickel), Cu (copper), Y (yttrium), Zr (zirconium), Nb (niobium), Mo (molybdenum), Tc (technetium), Ru (ruthenium), and Ag (silver); Among X, at least one selected from the group consisting of Cs, Rb, Ba, Sr, Ti, V, Cr, Mn, Fe, Co, Ni, Zr, Mo, Cu, Ag, and Au is preferred, and at least one selected from the group consisting of Cs and Rb is more preferred. By using these preferred elements, the HC desorption start temperature of the adsorbed HC can be increased. X can be supplied as, for example, sulfates, nitrates, acetates, chlorides, oxides, composite oxides, complex salts, and the like. Specific methods for this may be any method that allows X to be held at least in the ion exchange sites or pores of the MSE zeolite, and include, but are not limited to, ion exchange methods, evaporation to dryness methods, precipitation support methods, physical mixing methods, and impregnation support methods. Typically, MSE zeolite can be ion-exchanged to X type by performing liquid-phase treatment using an aqueous solution containing X. After the X-supporting treatment, if necessary, a solid-liquid separation treatment, a water washing treatment, a drying treatment for removing water at a temperature of about 50 to 150°C in the air, and the like can be carried out according to a conventional method. In addition, a treatment for reducing the amount of acid can also be carried out. The treatment for reducing the amount of acid can be carried out, for example, by silylation, steam treatment, dicarboxylic acid treatment, and the like. These treatments for reducing the amount of acid and changing the composition can be carried out according to a conventional method.

[0042] The amount of X supported can be appropriately set depending on the required performance and is not particularly limited, but the alumina ratio of X (X / Al) is preferably 0.10 or more and 1.50 or less, more preferably 0.30 or more and 1.25 or less, and even more preferably 0.50 or more and 1.00 or less, in terms of molar ratio.

[0043] In addition, the potassium ratio of X (X / K) can be appropriately set depending on the required performance and is not particularly limited, but is preferably 2.0 or more and 25.0 or less, more preferably 5.0 or more and 23.0 or less, and even more preferably 7.0 or more and 20.0 or less, in molar ratio.

[0044] Here, a preferred method for producing KX-supported MSE zeolite includes a method in which K-supported MSE zeolite is synthesized by hydrothermal synthesis in the presence of potassium, and X is added to this K-supported MSE zeolite by ion exchange to obtain KX-supported MSE zeolite. In this way, by using MSE zeolite (Brønsted acid type having protonic hydrogen atoms) on which potassium has already been supported by hydrothermal synthesis, and further adding X by ion exchange to obtain KX-supported MSE zeolite (Lewis acid type), the process is simplified and adjustment of the potassium to alumina ratio (K / Al), the X to alumina ratio (X / Al), and the X to potassium ratio (X / K), etc., is facilitated. From this viewpoint, in a preferred production method, MSE zeolite is dissolved in NH4 + It is preferable that the method does not have a separate step of ion-exchanging the MSE type zeolite into a zeolite having a high molecular weight (for example, a step of subjecting the MSE type zeolite to a liquid-phase treatment using an aqueous solution containing ammonium ions, such as an aqueous solution of ammonium nitrate or ammonium chloride).

[0045] The KX-supported MSE zeolite of the present invention is promising as a solid acid catalyst, and is also promising as a hydrocarbon adsorbent because of its relatively excellent heat resistance. More specifically, it is particularly promising as a catalyst for catalytic cracking of paraffin, for example, a cracking catalyst for long-chain hydrocarbons (e.g., hexane) in the petrochemical industry, and is also particularly promising as an HC trap for purifying exhaust gas from various internal combustion engines such as gasoline engines and diesel engines (e.g., diesel automobiles, gasoline automobiles, jet engines, boilers, gas turbines, etc.).

[0046] [HC trap for exhaust gas purification] The above-mentioned KX-supported MSE zeolite is particularly effectively used as a hydrocarbon adsorbent for exhaust gas, and can be implemented in various aspects. For example, the above-mentioned KX-supported MSE zeolite can be used as a powder. In addition, for example, the powder can be molded into an arbitrary shape to be used as a granular or pellet-shaped molded body. Note that, when preparing the molded body, various known dispersing devices, kneading devices, and molding devices can be used. Furthermore, the above-mentioned KX-supported MSE zeolite can be supported (supported) on a catalyst carrier such as a ceramic monolith carrier made of cordierite, silicon carbide, silicon nitride, etc., a metal honeycomb carrier or wire mesh carrier made of stainless steel, or a steel wool-like knit wire carrier. Note that, these can be used alone or in any combination and ratio of two or more. When the above-mentioned KX-supported MSE zeolite is supported on a catalyst carrier, various known coating methods, wash coat methods, and zone coat methods can be applied.

[0047] In particular, the above-mentioned KX-supported MSE zeolite can be used as an HC trap or an HC trap catalyst in various types of exhaust gas purification systems. The embodiment of the HC trap for exhaust gas purification is not particularly limited, but includes an embodiment that includes a honeycomb substrate and a hydrocarbon adsorption layer provided on and / or within the honeycomb substrate, and the hydrocarbon adsorption layer contains at least the above-mentioned exhaust gas hydrocarbon adsorbent (KX-supported MSE zeolite). By supporting the zeolite on a honeycomb substrate in this manner, the gas flow rate can be kept relatively high, thereby realizing an efficient HC trap.

[0048] The type of honeycomb substrate is not particularly limited as long as it can support the hydrocarbon adsorbent. Examples of the substrate include metals, alloys, plastics, ceramics, paper, synthetic paper, nonwoven fabrics, and laminates of these materials, but are not particularly limited thereto. The shape, planar shape, thickness, and the like of the honeycomb substrate may be appropriately set according to the application and required performance. For example, as a support for automobile exhaust gas applications, ceramic monolithic supports such as cordierite, silicon carbide, and silicon nitride, metal honeycomb supports such as stainless steel, wire mesh honeycomb supports such as stainless steel, and steel wool knit wire honeycomb supports, which are well known in the art, can be used. The outer shape of the substrate can be selected from any shape, such as a prismatic shape, a cylindrical shape, a spherical shape, a honeycomb shape, and a sheet shape. These can be used alone or in appropriate combination of two or more types. By using a honeycomb substrate as a support for the hydrocarbon adsorbent, it becomes easier to install the substrate in a gas flow.

[0049] The size of the honeycomb substrate is not particularly limited and can be appropriately set depending on the application and required performance. The number of holes in the openings of the honeycomb substrate may be appropriately set in consideration of the type of exhaust gas to be treated, the gas flow rate, pressure loss, removal efficiency, etc. The cell density is not particularly limited, but is usually 100 to 900 cells / inch from the viewpoint of maintaining a high surface area for the gas flow and suppressing an increase in pressure loss. 2(15.5~139.5 cells / cm 2 ) is preferable, and 200 to 600 cells / inch 2 (31-93 cells / cm 2 The cell density means the number of cells per unit area in a cross section of a honeycomb substrate cut perpendicularly to the gas flow path.

[0050] In addition, as a honeycomb type substrate for automobile exhaust gas, a flow-through type structure in which gas flow paths are connected, and a wall-flow type structure in which a part of the end face of the gas flow path is sealed and gas can flow through the wall of the gas flow path are widely known. In this embodiment, either type can be applied, but a flow-through type structure, which has low air resistance and low exhaust gas pressure loss, is preferably used.

[0051] The method of applying the above-mentioned KX-supported MSE zeolite to a catalyst carrier or a honeycomb substrate may be performed according to a conventional method, and is not particularly limited. As an example, the above-mentioned KX-supported MSE zeolite, an aqueous medium, and, if necessary, a binder known in the art, other catalysts, cocatalyst particles, OSC materials, base particles, additives, etc. are mixed in a desired mixing ratio to prepare a slurry (slurry-like mixture), and the obtained slurry-like mixture is applied to a catalyst carrier or a honeycomb substrate, and then, if necessary, dried or fired. At this time, if necessary, an acid or base may be mixed to adjust the pH, or a surfactant or a dispersion resin may be mixed to adjust the viscosity or improve the slurry dispersibility. As a method of mixing the slurry, crushing and mixing using a ball mill or the like can be applied, but other crushing or mixing methods can also be applied. The method of applying the slurry composition to a catalyst carrier or a honeycomb substrate may be performed according to a conventional method, and is not particularly limited. Various known coating methods, wash coat methods, and zone coat methods can be applied.

[0052] The amount of the slurry composition applied (coating amount) to the catalyst carrier or honeycomb substrate may be appropriately set depending on the required performance and is not particularly limited. From the viewpoint of the balance between NOx adsorption performance or catalytic performance and pressure drop, the amount is preferably 0.1 to 500 g / L, more preferably 10 to 400 g / L, and even more preferably 20 to 300 g / L, calculated as the composition of the above-mentioned catalyst slurry composition (calculated as Cu-containing zeolite).

[0053] After the application of the slurry composition, a drying treatment can be performed at about 50°C to 200°C for about 1 to 48 hours according to a conventional method, for example, by drying under reduced pressure using a vacuum dryer or the like. The slurry composition applied to the catalyst carrier or honeycomb-type substrate can also be subjected to a firing treatment, for example, by heat-treating the composition at 300°C to 1000°C. The firing temperature can be appropriately set according to the raw materials used, etc., and is not particularly limited, but is preferably 400°C to 900°C, more preferably 430°C to 800°C, and even more preferably 450°C to 750°C. The treatment time (firing time) in this firing treatment can be appropriately set according to the treatment temperature and economic efficiency, and is not particularly limited, but is usually 0.1 hours to 72 hours, preferably 0.2 hours to 48 hours, and more preferably 0.5 hours to 40 hours. The firing treatment is preferably performed in an oxygen-containing atmosphere, for example, in the air. The heating means is not particularly limited, and may be, for example, an electric furnace, a gas furnace, or any other known means in the art.

[0054] If necessary, platinum group elements (PGM: Platinum Group Metals) such as platinum, palladium, rhodium, and iridium, and transition metals such as Cu, Fe, W, and Ce may be mixed in the slurry composition and supported on the surface of the KX-supported MSE-type zeolite. These can function as catalytically active components for exhaust gas purification, and therefore can impart high catalytic performance to the hydrocarbon adsorption layer (hydrocarbon adsorption catalyst layer). From the viewpoint of catalytic activity, a preferred embodiment is a hydrocarbon adsorption catalyst layer containing one or more selected from the group consisting of Pt, Pd, and Rh. The supporting method can be a known method and is not particularly limited. For example, a solution of a salt containing a platinum group element or a transition metal element is prepared, the slurry composition (slurry composition for catalyst) is impregnated with this salt-containing solution, and then calcined, whereby the platinum group element or the transition metal element can be supported. The platinum group elements and transition metal elements can be supplied, for example, as an aqueous nitrate solution, a dinitrodiammine nitrate solution, an aqueous chloride solution, a sulfate, a nitrate, an acetate, a chloride, an oxide, a composite oxide, a complex salt, or the like, but are not particularly limited thereto.

[0055] In addition, other zeolites can be used in combination with the above-mentioned KX-supported MSE zeolite. Specific examples of other zeolites include SSF zeolite, MFI zeolite, MEL zeolite, MWW zeolite, *BEA zeolite, BEC zeolite, BIK zeolite, BOF zeolite, BOG zeolite, BRE zeolite, CAS zeolite, CDO zeolite, CFI zeolite, -CHI zeolite, CON zeolite, CSV zeolite, DAC zeolite, DDR zeolite, DOH zeolite, DON zeolite, EEI zeolite, and EON zeolite. , EPI type zeolite, ESV type zeolite, EUO type zeolite, *-EWT type zeolite, FER type zeolite, GON type zeolite, HEU type zeolite, IFR type zeolite, -IFU type zeolite, IFW type zeolite, IHW type zeolite, IMF type zeolite, IRN type zeolite, IRR type zeolite, -IRY type zeolite, ISV type zeolite, ITE type zeolite, ITG type zeolite, ITH type zeolite, *-ITN type zeolite, ITR type zeolite, ITT type zeolite, ITW type zeolite, I WR type zeolite, IWS type zeolite, IWV type zeolite, IWW type zeolite, LTF type zeolite, MAZ type zeolite, MEI type zeolite, MEP type zeolite, MFS type zeolite, MON type zeolite, MOR type zeolite, *MRE type zeolite, MTF type zeolite, MTN type zeolite, MTT type zeolite, MTW type zeolite, NES type zeolite, NON type zeolite, NSI type zeolite, OKO type zeolite, -PAR type zeolite, PCR type zeolite, POS type zeolite, RRO type zeolite zeolite, RSN type zeolite, RTE type zeolite, RTH type zeolite, RUT type zeolite, RWR type zeolite, SEW type zeolite, SFE type zeolite, SFF type zeolite, SFG type zeolite, SFH type zeolite, SFN type zeolite, SFS type zeolite, *SFV type zeolite, SGT type zeolite, SOF type zeolite, SSF type zeolite, *-SSO type zeolite, SSY type zeolite, STF type zeolite, STI type zeolite, *STO type zeolite, STT type zeolite, STW type zeolite,-SVR type zeolite, SVV type zeolite, SZR type zeolite, TER type zeolite, TON type zeolite, TUN type zeolite, UOS type zeolite, UOV type zeolite, UTL type zeolite, UWY type zeolite, VET type zeolite, VNI type zeolite, VSV type zeolite, YUG type zeolite, etc., but are not particularly limited to these. Note that these other zeolites can be used alone or in any combination and ratio of two or more.

[0056] (binder) Furthermore, if necessary, a binder may be contained. By blending a binder in the slurry composition, the coating strength of the resulting hydrocarbon adsorption layer (hydrocarbon adsorption layer) and the adhesion to the honeycomb substrate tend to be increased. Here, as the binder, a binder known in the art can be used, and the type is not particularly limited. Examples of the binder include boehmite, colloidal alumina, alumina sol, titania sol, silica sol, zirconia sol, etc., but are not particularly limited thereto. In addition, soluble salts such as aluminum nitrate, aluminum acetate, titanium nitrate, titanium acetate, zirconium nitrate, and zirconium acetate can also be used as the binder. In addition, acids such as acetic acid, nitric acid, hydrochloric acid, and sulfuric acid can also be used as the binder. The binder can be used alone or in any combination and ratio of two or more kinds.

[0057] The amount of the binder used is not particularly limited, and may be an amount necessary to maintain the coating strength and adhesion of the hydrocarbon adsorption layer (hydrocarbon adsorption layer). Specifically, the content of the binder is preferably 0.1 to 40 mass %, more preferably 1 to 35 mass %, and further preferably 2 to 30 mass %, based on the total amount of the slurry composition.

[0058] By the above-mentioned manufacturing method, it is possible to obtain a laminated structure HC trap for exhaust gas purification including at least a honeycomb substrate and a hydrocarbon adsorption layer provided on at least one surface thereof, and a laminated structure HC trap catalyst for exhaust gas purification including at least a honeycomb substrate and a hydrocarbon adsorption catalyst layer provided on at least one surface thereof. Here, in this specification, "provided on at least one surface of the honeycomb substrate" means that an arbitrary other layer (e.g., a primer layer, an adhesive layer, etc.) is interposed between one surface of the honeycomb substrate and the hydrocarbon adsorption layer. That is, in this specification, "provided on one surface" is used to mean both an embodiment in which the honeycomb substrate and the hydrocarbon adsorption layer are directly placed on each other, and an embodiment in which the honeycomb substrate and the hydrocarbon adsorption layer are arranged apart from each other through an arbitrary other layer. In addition, it means that the hydrocarbon adsorption layer may be provided on only one surface of the honeycomb substrate, or on multiple surfaces (e.g., one main surface and the other main surface, etc.). In this case, a honeycomb substrate is used, a laminated structure is placed in the flow path through which the gas flows, and the gas flows through the cells of the honeycomb substrate, thereby enabling highly efficient purification of exhaust gas.

[0059] In the laminated HC trap for purifying exhaust gas or the HC trap catalyst for purifying exhaust gas, the hydrocarbon adsorption layer or the hydrocarbon adsorption catalyst layer may be either a single layer or multiple layers. It may be a single layer of only the hydrocarbon adsorption layer, or it may be a single layer of only the hydrocarbon adsorption catalyst layer, or it may be a laminate of two or more hydrocarbon adsorption layers, or it may be a laminate of two or more hydrocarbon adsorption catalyst layers, or it may be a combination of a hydrocarbon adsorption layer and a hydrocarbon adsorption catalyst layer to form two or more layers, or it may be a combination of a hydrocarbon adsorption layer and a catalyst layer known in the art to form two or more layers, or it may be a combination of a layer known in the art and a hydrocarbon adsorption catalyst layer to form two or more layers. In this case, the coating amount of the above-mentioned hydrocarbon adsorption layer is not particularly limited, but from the viewpoint of the balance between catalyst performance and pressure drop, etc., based on the unit volume (1 L) of the catalyst carrier or honeycomb type substrate or honeycomb type substrate, the coating amount is preferably 1 g / L or more and 150 g / L, more preferably 3 g / L or more and 135 g / L, and even more preferably 5 g / L or more and 120 g / L, calculated in terms of the solid content of the above-mentioned KX-supported MSE type zeolite.

[0060] The above-mentioned HC trap for purifying exhaust gas (HC trap catalyst for exhaust gas purification) can be arranged in the exhaust system of various internal combustion engines. The number and locations of the HC traps for purifying exhaust gas (HC trap catalyst for exhaust gas purification) to be installed can be appropriately designed according to exhaust gas regulations. According to the HC trap for purifying exhaust gas (HC trap catalyst for exhaust gas purification) of this embodiment, the HC desorption start temperature of the adsorbed HC is high, and high HC purification performance can be exhibited at the time of cold start, thereby realizing an exhaust gas purification system with excellent purification performance. According to a preferred embodiment of the present invention, such high-performance hydrocarbon adsorbent for exhaust gas, HC trap for purifying exhaust gas (HC trap catalyst for exhaust gas purification), and exhaust gas purification system can be supplied by an industrially simple process and at a relatively low cost. EXAMPLES

[0061] The features of the present invention will be described in more detail below with reference to test examples, examples and comparative examples, but the present invention is not limited by these. That is, the materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. In addition, the values ​​of various manufacturing conditions and evaluation results in the following examples have the meaning of preferred upper limit values ​​or preferred lower limit values ​​in the embodiment of the present invention, and the preferred range may be a range defined by a combination of the above-mentioned upper limit value or lower limit value and the values ​​of the following examples or the values ​​of the examples.

[0062] (Production Example 1) Synthesis of OSDA First, N-N'-diethylbicyclo[2.2.2]oct-7-ene-2,3:5,6-tetracarboxyl diimide was synthesized from bicyclo[2.2.2]oct-7-ene-2,3:5,6-tetracarboxylic dianhydride (manufactured by Tokyo Chemical Industry Co., Ltd.) according to the method described in JP 2020-050611 A. Next, N,N,N',N'-tetraethylbicyclo[2.2.2]oct-7-ene-2,3:5,6-dipyrrolidinium diiodide was synthesized according to the method described in JP 6430303 A.

[0063] (Preparation Example 1) Synthesis of MSE-type zeolite Next, MSE-type zeolite was synthesized according to the method described in T. Shibata et al., Microporous and Mesoporous Materials, 116 (2008) 216. A solution of 102.5 g of colloidal silica (Snowtex N40, Nissan Chemical Co., Ltd.), 157.0 g of water, 6.0 g of aluminum hydroxide gel (Kyoward KW200S, Kyowa Chemical Co., Ltd.), and 10 g of potassium hydroxide (Fujifilm Wako Pure Chemical Co., Ltd.) dissolved in 90 g of water was mixed with 40.1 g of N,N,N',N'-tetraethylbicyclo[2.2.2]oct-7-ene-2,3:5,6-dipyrrolidinium diiodide of Production Example 1, and stirred for 16 hours in a stainless steel beaker. The composition of the mixture was as follows. The numerical values ​​in the following compositions represent the ratio of the amount of material when the amount of material of SiO2 is set to 1. SiO2 0.051 Al2O3 0.100 OSDA 0.375 KOH 30.00 H2O

[0064] Next, this raw material composition (mixture) was divided and charged into two 300cc PTFE pressure-resistant sealed containers and left to stand at 160°C for 384 hours. The product after this hydrothermal treatment was separated into solid and liquid, and the obtained solid phase was washed with water and dried at 105°C to obtain a product. The entire amount of the obtained product was calcined at 600°C for 5 hours while circulating air. The product obtained in this manner was subjected to powder fluorescent X-ray analysis (XRD: X-ray diffraction) using a powder fluorescent X-ray analyzer (Bruker Japan Co., Ltd., D8 Advance), and it was confirmed that it was a single-phase MSE-type zeolite (SAR: 20, crystallite size: 62nm, average particle size D50: 14μm). In addition, elemental analysis was performed by the ICP method using an ICP emission analyzer (Shimadzu Corporation, ICPS-8100), and the molar ratio was K / Al = 0.35.

[0065] (Example 1) Cs-K supported MSE type zeolite 5.0 g of the calcined MSE zeolite of Preparation Example 1 was added to an aqueous solution in which 5.0 g of cesium acetate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in 100 g of water, and the solution was heated and stirred, and then held at 80°C for 3 hours. After cooling, the solution was filtered, and the same operation was repeated once more. Then, the solution was washed with water and dried at 105°C for 16 hours to obtain the Cs-K-supported MSE zeolite of Example 1. The obtained Cs-K-supported MSE zeolite of Example 1 was subjected to elemental analysis measurement by the ICP method using an ICP emission spectrometer (Shimadzu Corporation, ICPS-8100, and Thermo Fisher Scientific Japan Co., Ltd. iCAP6500), and the molar ratios were K / Al=0.06 and Cs / Al= 0.76, Cs / K=13.6. The obtained Cs-K supported MSE type zeolite of Example 1 was wet-coated onto a honeycomb substrate in an amount of 100 g per 1 L of the honeycomb substrate, and then fired at 500° C. to obtain an HC trap for exhaust gas purification of Example 1 in which a hydrocarbon adsorption layer containing the Cs-K supported MSE type zeolite was provided on the honeycomb substrate.

[0066] In order to evaluate the HC adsorption performance of the Cs-K supported MSE type zeolite of Example 1, toluene adsorption / desorption measurements were carried out. Here, Cs-K supported MSE type zeolite was separated, and a TPR (Temperature Programmed Reaction) measuring device (Microtrack Bell Corporation BELCAT-A, BEL-Mass) was used to measure the adsorption and desorption of toluene in a Gas-1 (5% Ar, balance He) atmosphere with a saturated vapor pressure setting temperature of 80 ° C (saturated vapor pressure 47377 Pa) and a flow rate of 300 cc / min. The gas was heated from 70 ° C to 600 ° C at 30 ° C / min, then cooled to 600 ° C to 70 ° C, and held at 70 ° C for 10 minutes. Then, the gas was switched to Gas-2 (5% Ar, 2% H2O, 0.007% toluene (500 ppm C toluene), balance He) with a flow rate of 300 cc / min, and the temperature was raised from 70 ° C to 600 ° C at 10 ° C / min. The toluene desorption temperature was 192 ° C.

[0067] (Comparative Example 1) KH-type MSE-type zeolite The calcined MSE zeolite of Preparation Example 1 was used as it was as Comparative Example 1. The KH MSE zeolite of Comparative Example 1 was subjected to elemental analysis measurement by ICP method using an ICP emission spectrometer (Shimadzu Corporation, ICPS-8100), and the molar ratio was K / Al=0.35. In addition, a toluene adsorption / desorption test was performed in the same manner as in Example 1, and the toluene desorption temperature was 178°C.

[0068] (Comparative Example 2) K-type MSE zeolite 5.0 g of the calcined MSE zeolite of Preparation Example 1 was added to an aqueous solution in which 2.5 g of potassium acetate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in 100 g of water, and the mixture was heated and stirred, and held at 80°C for 3 hours. After cooling, the mixture was filtered, and the same operation was repeated once more. Then, the mixture was washed with water and dried at 105°C for 16 hours to obtain K-type MSE zeolite of Comparative Example 2. The K-type MSE zeolite of Comparative Example 2 was subjected to elemental analysis measurement by the ICP method using an ICP emission spectrometer (Shimadzu Corporation, ICPS-8100, and Thermo Fisher Scientific Co., Ltd. iCAP6500), and the molar ratio was K / Al = 0.73. In addition, a toluene adsorption / desorption test was performed in the same manner as in Example 1, and the toluene desorption temperature was 168°C.

[0069] (Comparative example 3)H + MSE type zeolite 10.0 g of the calcined MSE zeolite of Preparation Example 1 was added to an aqueous solution of 15.0 g of ammonium nitrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) dissolved in 115 g of water, heated and stirred, and held at 80°C for 3 hours. After cooling, the mixture was filtered, and the same procedure was repeated once more. The mixture was then washed with water, dried at 105°C for 16 hours, and dehydrated with NH4 + The MSE type zeolite was obtained. The obtained NH4 + The MSE type zeolite was calcined at 500° C. for 5 hours to obtain the H + The MSE type zeolite was obtained. + The MSE type zeolite was subjected to elemental analysis by the ICP method using an ICP emission spectrometer (Shimadzu Corporation, ICPS-8100), and the molar ratio was K / Al=0.07. In addition, a toluene adsorption / desorption test was performed in the same manner as in Example 1, and the toluene desorption temperature was 141°C.

[0070] (Comparative Example 4) Cs-K supported MSE type zeolite Comparative Example 3 H +5.0 g of MSE zeolite was added to an aqueous solution in which 5.0 g of cesium acetate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in 100 g of water, and the solution was heated and stirred, and then held at 80°C for 3 hours. After cooling, the solution was filtered, and the same operation was repeated once more. Then, the solution was washed with water and dried at 105°C for 16 hours to obtain the Cs-K-supported MSE zeolite of Comparative Example 4. The Cs-K-supported MSE zeolite of Comparative Example 4 was subjected to elemental analysis measurement by the ICP method using an ICP emission spectrometer (Shimadzu Corporation, ICPS-8100, and Thermo Fisher Scientific Japan Co., Ltd. iCAP6500), and the molar ratios were K / Al=0.03 and Cs / Al= 0.75 , Cs / K=26.5. When a toluene adsorption / desorption test was carried out in the same manner as in Example 1, the toluene desorption temperature was 180°C.

[0071] (Comparative Example 5) Cs-type FAU-type zeolite 400 g of FAU type zeolite (HSZ-350HUA, SAR: 11, manufactured by Tosoh Corporation) was added to an aqueous solution in which 147 g of 60 wt % nitric acid (manufactured by Kanto Chemical Co., Ltd.) was dissolved in 4000 g of water, and the solution was heated and stirred, and held at 80 ° C. for 3 hours. After cooling, the solution was filtered, washed with water, and then dried at 105 ° C. to obtain FAU type zeolite (SAR: 19). 20.0 g of the obtained FAU type zeolite was added to an aqueous solution in which 20.0 g of cesium acetate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in 550 g of water, and the solution was heated and stirred, and held at 80 ° C. for 3 hours. After cooling, the solution was filtered, and then the same operation was repeated once again. After that, the solution was washed with water and dried at 105 ° C. for 16 hours to obtain Cs type FAU type zeolite of Comparative Example 5. In addition, a toluene adsorption and desorption test was performed in the same manner as in Example 1, and the toluene desorption temperature was 161 ° C.

[0072] (Comparative Example 6) Cs-type MFI zeolite MFI type zeolite was synthesized with reference to High-Al ZSM-5 described in IZA SYNTHESIS COMMISION, and ion exchange to Cs type was carried out as follows. 1.5 g of 40 mass% tetrapropylammonium hydroxide solution (manufactured by Seikemui Co., Ltd.), 7.2 g of 4.8 mass% sodium hydroxide solution, and 12.8 g of water were mixed and stirred in a SUS beaker. 3.8 g of amorphous silica Nipsil ER (manufactured by Tosoh Silica Co., Ltd.) was added little by little to this. After stirring for 1 hour, the resulting mixture was placed in a 100 cc PTFE pressure vessel and held at 100 ° C for 16 hours, and 25.3 g of seeding gel was obtained. 9.1 g of the obtained seeding gel was mixed with 1.3 g of aluminum hydroxide gel (Kyoward KW200S, manufactured by Kyowa Chemical Industry Co., Ltd.), 73.1 g of 4.8 mass% sodium hydroxide, 87.7 g of water, and 19.2 g of amorphous silica (Nipsil ER, manufactured by Tosoh Corporation) and stirred for 1 hour. The composition of the mixture was as follows. The numerical values ​​in the following compositions represent the ratio of the amount of material when the amount of material of SiO2 is set to 1. SiO2 0.025 Al2O3 0.017 OSDA 0.145 Na2O 29.66 H2O

[0073] Next, this raw material composition (mixture) was divided and charged into two 300cc PTFE pressure-resistant sealed containers, and left to stand at 175°C for 48 hours. The product after this hydrothermal treatment was separated into solid and liquid, and the obtained solid phase was washed with water and dried at 105°C to obtain a product. The entire amount of the obtained product was calcined at 600°C for 5 hours while circulating air. The product obtained in this manner was subjected to powder fluorescent X-ray analysis (XRD: X-ray diffraction) using a powder fluorescent X-ray analyzer (Bruker Japan Co., Ltd., D8 Advance), and it was confirmed to be a single-phase MFI type zeolite (SAR: 40). 10.0 g of the obtained calcined MFI type zeolite was added to an aqueous solution in which 15.0 g of ammonium nitrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in 115 g of water, and the mixture was heated and stirred, and held at 80°C for 3 hours. After cooling, it was filtered, and then the same operation was repeated once again. After that, it was washed with water and dried at 105°C for 16 hours. + This was calcined at 500°C for 5 hours to obtain MFI type zeolite. + The resulting MFI type zeolite was + 5.0 g of MFI zeolite was added to an aqueous solution in which 5.0 g of cesium acetate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in 100 g of water, and the solution was heated and stirred, and then held at 80°C for 3 hours. After cooling, the solution was filtered, and the same operation was repeated once more. After washing with water, the solution was dried at 105°C for 16 hours to obtain the Cs-type MFI zeolite of Comparative Example 6. In addition, a toluene adsorption / desorption test was performed in the same manner as in Example 1, and the toluene desorption temperature was 172°C.

[0074] (Comparative Example 7) Cs-type MFI zeolite The amount of seeding gel was 8.7 g, the amount of aluminum hydroxide gel (Kyoward KW200S, manufactured by Kyowa Chemical Industry Co., Ltd.) was 2.6 g, the amount of 4.8 wt% sodium hydroxide was 71.1 g, the amount of water was 84.9 g, and the amount of amorphous silica (Nipsil ER, manufactured by Tosoh Corporation) was 18.7 g. Except for changing the composition of the mixture as follows, MFI type zeolite (SAR: 20) was synthesized in the same manner as in Comparative Example 6. The composition of the mixture was as follows. The numerical values ​​in the following compositions represent the substance amount ratio when the substance amount of SiO2 is 1. SiO2 0.050 Al2O3 0.017 OSDA 0.145 Na2O 29.66 H2O The results of XRD showed that a small amount of MOR was by-produced. Thereafter, heat treatment, calcination treatment, and ion exchange treatment were performed in the same manner as in Comparative Example 6 to obtain a Cs-type MFI zeolite of Comparative Example 7. In addition, a toluene adsorption / desorption test was performed in the same manner as in Example 1, and the toluene desorption temperature was 172°C.

[0075] The evaluation results are shown in Table 1. [Table 1] [Industrial Applicability]

[0076] The KX-supported MSE zeolite of the present invention can be widely and effectively used as a solid acid catalyst for catalytic cracking of paraffin, and a hydrocarbon adsorbent or a hydrocarbon adsorption catalyst for hydrocarbons (HC), and can be particularly effectively used in HC traps for exhaust gas purification or HC trap catalysts for exhaust gas purification and exhaust gas purification systems for various internal combustion engines such as gasoline engines and diesel engines.

Claims

1. The present invention comprises at least an MSE zeolite, potassium supported on the MSE zeolite, and X (wherein X is Cs), The silica-alumina ratio of the MSE zeolite (SiO 2 / Al 2 O 3 ) is in a molar ratio of 10 or more and 100 or less, The potassium ratio of X (X / K) is 2.0 or more and 25.0 or less in molar ratio; Hydrocarbon adsorbent for exhaust gas.

2. The potassium to alumina ratio (K / Al) is 0.04 or more and 0.50 or less in molar ratio. The adsorbent for exhaust gas hydrocarbons according to claim 1.

3. The alumina ratio of X (X / Al) is 0.10 or more and 1.50 or less in terms of molar ratio. The adsorbent for exhaust gas hydrocarbons according to claim 1 or 2.

4. In powder X-ray diffraction measurement, the crystallite size is 10 nm or more and 100 nm or less. The adsorbent for exhaust gas hydrocarbons according to any one of claims 1 to 3.

5. The average particle size D50 is 0.01 μm or more and 20 μm or less. The adsorbent for exhaust gas hydrocarbons according to any one of claims 1 to 4.

6. An HC trap for exhaust gas purification used in an exhaust gas purification system for purifying exhaust gas from an internal combustion engine, A honeycomb-type substrate and a hydrocarbon adsorption layer provided on and / or within the honeycomb-type substrate, The hydrocarbon adsorption layer contains at least the exhaust gas hydrocarbon adsorbent according to any one of claims 1 to 5. HC trap for exhaust gas purification.

7. The hydrocarbon adsorption layer contains the exhaust gas hydrocarbon adsorbent in an amount of 1 g / L or more and 150 g / L or less based on a unit volume (1 L) of the honeycomb substrate.

7. The HC trap for purifying exhaust gas according to claim 6.

8. The hydrocarbon adsorption layer is a hydrocarbon adsorption catalyst layer containing one or more precious metal components selected from the group consisting of Pt, Pd, and Rh.

8. An HC trap for purifying exhaust gas according to claim 6 or 7.

9. Further comprising a catalyst layer The HC trap for purifying exhaust gas according to any one of claims 6 to 8.

10. Providing a K-loaded MSE zeolite; and The method includes at least a step of adding X (wherein X is Cs) to a K-supported MSE zeolite to synthesize a K-X-supported MSE zeolite having a silica-alumina ratio (SiO 2 / Al 2 O 3 ) of 10 or more and 100 or less in molar ratio and a potassium ratio (X / K) of X of 2.0 or more and 25.0 or less in molar ratio. A method for producing KX-supported MSE type zeolite.

11. In the step of synthesizing the K-X-supported MSE zeolite, the K-supported MSE zeolite is supported by an ion exchange method. The method for producing the K-X-supported MSE zeolite according to claim 10.

12. In the step of preparing the K-supported MSE zeolite, the K-supported MSE zeolite is synthesized by a hydrothermal synthesis method in the presence of potassium. The method for producing the KX-supported MSE zeolite according to claim 10 or 11.

Citation Information

Patent Citations

  • Gas component reducing material and hydrocarbon adsorbing material

    JP2002001109A

  • Hydrocarbon adsorbent for exhaust gas and exhaust gas cleaning catalyst using it

    JP2004105821A

  • Hydrocarbon trap / catalyst composition

    JP2004504130A

  • HC adsorbing purification catalyst

    JP2006297375A

  • Oxidation catalyst

    JP2013517935A